An Economic Study to Estimate Post Harvest Losses of Tomatoes Crop in The Green Mountain Region - Ifhima, Joma A.; Tolba, Adly S.; Omar, Soad S. (Al-Mukhtar Journal of Sciences, 2007)
The study focused on the main factors affecting the increase in the post harvest losses of tomatoes ,the post harvest losses of the study crop reached about 15% of total production , the reducing of these losses will must increase the producers income with 1.9 thousand Denars , the study deals with estimating the marketing losses at the farm and retailer market levels of the tomatoes crop ,the study concerned with the quantitative analysis of the different factors affecting post harvest losses ratio using multi-regression analysis, The study shows that crop quantity , average from price has a statistically significant negative relationship post harvest ratio of tomatoes ,the study presents some of recommendation to help in reducing the losses of the studied crop .